Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions


(x-6) (x+6) =0      { a^2-b^2= (a+b)(a-b)
x=6, x=-6

1 5 1
plz mark as best
thank you kaushik thanks a lot thanks plz help me in others too i have a such a bad faculty in our school
The Brainliest Answer!
X²=36⇒x²-6²=0 then (x-6)(x+6)=0 now x-6=0 or x+6=0 Hence, x=+6 or -6
2 5 2
thanks jackie help me in others too
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts